Phase Transformation Behavior and Stability of LiNiO2 Cathode Material for Li‐Ion Batteries Obtained from In Situ Gas Analysis and Operando X‐Ray Diffraction. Issue 10 (4th April 2019) - de Biasi, Lea; Schiele, Alexander; Roca‐Ayats, Maria; Garcia, Grecia; Brezesinski, Torsten; Hartmann, Pascal; Janek, Jürgen
Abstract: Ni‐rich layered oxide cathode materials, in particular the end member LiNiO2, suffer from drawbacks such as high surface reactivity and severe structural changes during de‐/lithiation, leading to accelerated degradation and limiting practical implementation of these otherwise highly promising electrode materials in Li‐ion batteries. Among all known phase transformations occurring in LiNiO2, the one from the H2 phase to the H3 phase at high state of charge is believed to have the most detrimental impact on the material's stability. In this work, the multistep phase transformation process and associated effects are analyzed by galvanostatic cycling, operando X‐ray diffraction, and in situ pressure and gas analysis. The combined results provide thorough insights into the structural changes and how they affect the stability of LiNiO2 . During the H2–H3 transformation, the most significant change occurs in the c ‐lattice parameter, resulting in large mechanical stress in LiNiO2 . As for electrochemical stability, it suffers strongly in the H3 region. Oxygen evolution is observed not only during charge but also during discharge and found to be correlated with the presence of the H2 and H3 phases. Taken together, the experimental data improve the understanding of the degradation processes and the inherent instability of LiNiO2 in Li‐ion cells when operated above around 75 % state of charge. Abstract : Phases caught in the act : New insights into the structural evolution, the gassing behavior, and the cycling stability of LiNiO2, a promising next‐generation cathode active material for use in Li‐ion batteries, are gained from the combination of electrochemical charge/discharge experiments with different in situ analytical tools, such as X‐ray diffraction and differential electrochemical mass spectrometry.